Pragmatic Competence in Requests : A Case of Thai English Teachers - YARANG, MR. IMRON (2016)
This research describes the use of request strategies in influenced by differences of social status (S) and social distance (D) by Thai English teachers. This involved descriptive qualitative research in which the research participants were fourteen Thai English teachers,they were teachers in school who have teaching English at junior and senior high school. The data were spoken utterances of request strategies elicited though Discourse Completion Test (DCT) scenarios. The subjects were taken using the technique of proporsional random sampling comprising seven male and seven female participants. The research findings showed that Thai English teachers tended to express ability when they made requests. Social Status (S), difference than social distance (D), tended to influence the strategies of request.